2007
DOI: 10.1038/sj.ejcn.1602921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium supplementation on lipid profile in overweight or obese Iranian women: a double-blind randomized clinical trial

Abstract: Background: There is some evidence that suggests a beneficial effect of calcium intake on serum lipid profile. The objective of this study was to determine the effect of 1000 mg calcium supplementation for 30 days on serum lipid profile in overweight or obese women. Methods: A double-blind, randomized clinical trial was conducted in 44 overweight or obese adult women (body mass index (BMI) X25 kg m À2 , age: 2576y) receiving 1000 mg elemental calcium daily (n ¼ 24) or placebo (n ¼ 20). Serum lipids, lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“…Several [5, 1017], but not all [1821], clinical trials of calcium and serum lipids reported that supplemental calcium lowered serum total and LDL-cholesterol and increased HDL-cholesterol levels. Findings from human studies of calcium and circulating triglycerides have been inconsistent, with most studies finding no beneficial effects of calcium supplementation [5, 10, 11, 13, 1618, 20, 21]. In addition, calcium treatment was found to reduce blood pressure in rats [22], and a previous meta-analysis of randomized, placebo-controlled clinical trials suggested that calcium supplementation may lead to a small reduction in systolic blood pressure in humans [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Several [5, 1017], but not all [1821], clinical trials of calcium and serum lipids reported that supplemental calcium lowered serum total and LDL-cholesterol and increased HDL-cholesterol levels. Findings from human studies of calcium and circulating triglycerides have been inconsistent, with most studies finding no beneficial effects of calcium supplementation [5, 10, 11, 13, 1618, 20, 21]. In addition, calcium treatment was found to reduce blood pressure in rats [22], and a previous meta-analysis of randomized, placebo-controlled clinical trials suggested that calcium supplementation may lead to a small reduction in systolic blood pressure in humans [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…O aumento do cálcio sérico (p<0,001), mesmo após ajuste para idade, atividade física, álcool, ingestão de vitamina D e cálcio, e hábito de fumar, estava envolvido com todos os componentes da síndrome metabólica, exceto com a lipoproteína de alta densidade (HDL colesterol) 21 . Foi visto que a suplementação de 1000 mg de cálcio/dia, divididos em quatro cápsulas de carbonato de cálcio, não tem efeitos consideráveis sobre o perfil lipídico favorável nas mulheres com sobrepeso ou obesidade, no entanto, poderia ter um efeito preventivo sobre a elevação do colesterol total 22 . Outro trabalho examinou os efeitos em curto prazo de uma ingestão dietética alta e baixa de cálcio em combinação com dietas isoenergéticas com alto e baixo teor de gordura, sobre o perfil lipídico e a excreção fecal de gordura e ácidos biliares.…”
Section: Discussionunclassified
“…Some studies report that supplemental Ca may cause beneficial changes in circulating lipids (73,74) , whereas several studies found no effect (75)(76)(77)(78) . In contrast, Ca supplementation as compared with placebo for 12 months improved the lipid profile in a randomisedcontrolled trial of postmenopausal women, and this improvement was still observed at the 3-year follow-up (73) .…”
Section: Discussionmentioning
confidence: 99%